A natureza das substâncias de referência na avaliação de massas molares de resinas PBLH por meio de cromatografia de exclusão por tamanho e osmometria de pressão de vapor - Takahashi,Marta Ferreira Koyama (1997)
The SEC and VPO behaviour of hydroxyl-terminated polybutadiene resins was investigated using toluene as solvent and polybutadiene and polystyrene as standards. The results show that molar mass obtained depend on the nature of the standards used in the calibration, specialy in SEC analysis.